Mental Health Challenges, Parenting Stress, and Features of the Couple Relationship in Parents of Children With Fragile X Syndrome - Potter, Sarah Nelson; Harvey, Danielle J.; Sterling, Audra; Abbeduto, Leonard (Frontiers in Psychiatry, 2022)
Background Individuals with fragile X syndrome (FXS) have significant delays in cognition and language, as well as anxiety, symptoms of autism spectrum disorder, and challenging behaviors such as hyperactivity and aggression. Biological mothers of children with FXS, who are themselves FMR1 premutation or full mutation carriers, are at elevated risk for mental health challenges in addition to experiencing stress associated with parenting a child with significant disabilities. However, little is known about fathers in these families, including the ways in which parental well-being influences the mother-father relationship and the impact of child characteristics on paternal and couple functioning. Method The current study examined features of, and relationships between, parental well-being, couple well-being, and child functioning in 23 families of young boys with FXS. Mothers and fathers independently completed multiple questionnaires about their individual well-being, couple functioning, and child behavior. One parent per family also completed an interview about the child’s adaptive skills. Results Results suggest that both mothers and fathers in these families experience clinically significant levels of mental health challenges and elevated rates of parenting stress relative to the general population. Findings also indicate that the couples’ relationship may be a source of strength that potentially buffers against some of the daily stressors faced by these families. Additionally, parents who reported less parenting stress had higher couples satisfaction and dyadic coping. Finally, parents of children with less severe challenging behaviors exhibited fewer mental health challenges, less parenting stress, and higher levels of both couples satisfaction and dyadic coping. Parents of children with higher levels of adaptive behavior also reported less parenting stress and higher couples satisfaction. Conclusion Overall, this study provides evidence that families of children with FXS need access to services that not only target improvements in the child’s functioning, but also ameliorate parental stress. Family-based services that include both mothers and fathers would lead to better outcomes for all family members.